Initial damage and failure load of zirconia-ceramic and metal-ceramic posterior cantilever fixed partial dentures - Bömicke, Wolfgang; Boisserée, Philipp; Rammelsberg, Peter; Rues, Stefan (Clinical oral investigations, 2024)
Objectives: The aim of this study was to compare failure load and initial damage in monolithic, partially veneered, and completely veneered (translucent) zirconia cantilevered fixed partial dentures (CFPDs), as well as completely veneered metal-ceramic CFPDs under different support and loading configurations. Materials and methods: Eight test groups with anatomically congruent CFPDs (n = 8/group) were fabricated, differing in CFPD material/support structure/loading direction (load applied via steel ball (Ø 6 mm) 3 mm from the distal end of the pontic for axial loading with a 2-point contact on the inner cusp ridges of the buccal and oral cusps and 1.3 mm below the oral cusp tip for 30° oblique loading): (1) monolithic zirconia/CoCr abutment teeth/axial, (2) monolithic zirconia/CoCr abutment teeth/oblique, (3) partially veneered zirconia/CoCr abutment teeth/axial, (4) partially veneered zirconia/CoCr abutment teeth/oblique, (5) completely veneered zirconia/CoCr abutment teeth/axial, (6) completely veneered CoCr/CoCr abutment teeth/axial (control group), (7) partially veneered zirconia/implants/axial, and (8) partially veneered zirconia/natural teeth/axial. Restorations were artificially aged before failure testing. Statistical analysis was conducted using one-way ANOVA and Tukey post hoc tests. Results: Mean failure loads ranged from 392 N (group 8) to 1181 N (group 1). Axially loaded monolithic zirconia CFPDs (group 1) and controls (group 6) showed significantly higher failure loads. Oblique loading significantly reduced failure loads for monolithic zirconia CFPDs (group 2). Initial damage was observed in all groups except monolithic zirconia groups, and fractography revealed design flaws (sharp edges at the occlusal boundary of the veneering window) in partially veneered zirconia CFPDs. Conclusions: Monolithic zirconia CFPDs might be a viable alternative to completely veneered CoCr CFPDs in terms of fracture load. However, oblique loading of monolithic zirconia CFPDs should be avoided in clinical scenarios. Design improvements are required for partially veneered zirconia CFPDs to enhance their load-bearing capacity. Clinical relevance: Monolithic zirconia may represent a viable all-ceramic alternative to the established metal-ceramic option for CFPD fabrication. However, in daily clinical practice, careful occlusal adjustment and regular monitoring should ensure that oblique loading of the cantilever is avoided.